2012
DOI: 10.1007/s00705-012-1494-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of hepatitis E virus infection in schizophrenia

Abstract: Until now, the risk of HEV infection in schizophrenia was unknown. The present results showed that the seroprevalence of anti-HEV IgG and anti-HEV IgM in schizophrenia were significantly higher than that in healthy controls. Anti-HEV IgG positivity increased with age and with the duration of disease in schizophrenia patients. Moreover, schizophrenia patients with increased CD4(+)/CD8(+) T-cell ratios (>2.03) had higher anti-HEV IgG detection rates than those with normal ratios (1.05-2.03). Compared with the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…In previous studies in China and Germany, significantly higher prevalences of HEV infection were reported in inpatients with schizophrenia than in normal subjects. 3,4 The prevalence of HEV infection in patients with schizophrenia found in our study is much higher than that reported in previous studies. Altogether, these studies indicate that psychiatric patients have a higher HEV prevalence than control subjects.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In previous studies in China and Germany, significantly higher prevalences of HEV infection were reported in inpatients with schizophrenia than in normal subjects. 3,4 The prevalence of HEV infection in patients with schizophrenia found in our study is much higher than that reported in previous studies. Altogether, these studies indicate that psychiatric patients have a higher HEV prevalence than control subjects.…”
Section: Discussioncontrasting
confidence: 67%
“…1,2 Large waterborne outbreaks of HEV infection often occur explosively in areas where sanitary conditions are poor and the hygiene infrastructure is underdeveloped. 2 Immune-compromised individuals and institutionalized patients are at high risk of suffering from infectious diseases, including hepatitis E. 3 Nevertheless, studies on the prevalence of HEV infection among psychiatric patients are extremely limited. [3][4][5] Thus, we conducted a case-control study to estimate the seroprevalence of HEV infection and the potential risk factors for acquiring HEV infection in psychiatric patients in Shandong Province, eastern China.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published Chinese study reported significant differences in the HEV IgG seroprevalence rate according to the type of psychiatric disorder. The highest positivity was found in patients with mental and behavioural disorders due to the use of alcohol and drugs, as well as in patients with schizophrenia (Xue et al., ). In a German study, the highest prevalence was reported from patients hospitalized in wards for addiction therapy, including alcohol abusers and IDUs (Reinheimer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a higher prevalence of hepatitis E in patients with psychiatric disorders. Cong et al (34) recorded a seroprevalence of 27.19% and Xue et al (35) a seroprevalence of 34.9% in one population in China taking overall psychiatric disorders into consideration in the first study and schizophrenia in the second.…”
Section: Discussionmentioning
confidence: 99%